Implementation Of Character Education In Elementary Schools Through Educational Games - Basri, Amin (Jurnal Pendidikan, Kesehatan dan Olahraga, 2024)
Character education in elementary schools is a crucial aspect of shaping a high-quality young generation. One effective method for instilling character values is through educational games. These games are not only enjoyable but also serve as a medium for teaching moral and social values to children. Character education for children serves as a foundation for their future, functioning as the basis for self-discipline and as a tool for behavior control. The importance of character education has become a serious issue that needs immediate attention, as character education represents the strength of a nation. Education is an effort to humanize humans, which is the most important aspect of human life. This implies that every human being has the right to receive it and is expected to continuously develop within it. The type of research employed in this study is literature review. The literature review method involves a series of activities related to data collection from literature, reading and taking notes, as well as processing research materials. Literature review is a mandatory activity in research, especially academic research whose primary objective is to develop theoretical aspects or practical benefits. Character education in elementary schools is a crucial aspect of shaping a high-quality young generation. One effective method for instilling character values is through educational games. These games are not only enjoyable but also serve as a medium for teaching moral and social values to children. One method to create a fun and comfortable learning environment is through games. With an educational game approach, students can learn while having fun, aiming to develop their talents and shape positive character